Model and the Success of Financial Immunity in Community : Case Study of Saopao Community Welfare Fund, Sichon District, Nakhon Si Thammarat - Charungsutjaritkul, Wichit; Suknu, Pornpen; Na Nakorn, Chadaphorn (Parichart Journal, 2020)
This research article aimed to (1) study the state of financial immunity of the community; (2) compare the success of the financial immunization of the fund which classified by financial conditional level; 3) analyze the components of financial immunization; and (4) finding a model for community financial immunization by asking a sample of 300 people and a focus group. The results of the success of the financial immunity of the community found that most of the financial condition level were at the medium level (7 - 15 points). The results of comparison of differences of opinions towards fund management found that factors that had significant statistically differences were (1) the committee has management skills and expertise; (2) community welfare members had a shared ownership awareness; and (3) participation in learning exchange activities. The analysis of the components of financial immunization of the community using Principal Component Analysis Method which extracting important variables were (1) immunity; (2) cognitive understanding; (3) integration linking; (4) management model to be revenue; and (5) development and improving the quality of life. Finally, to combine all the data in qualitative data analysis and confirm the data using the triangular technique then summarize it into the model and the success of the community financial immunity.